Melanoma causes phenotypic modulations and metabolic switches of iNKT cells influencing clinical outcomes - Degeorges, Emmanuelle; Mouret, Stéphane; Girard, Pauline; Niveau, Camille; Cettour-Cave, Mélanie; Sosa Cuevas, Eleonora; De Fraipont, Florence; Charles, Julie; Saas, Philippe; Aspord, Caroline (Frontiers in Immunology, 2026)
IntroductionInvariant NKT (iNKT) cells are crucial effectors in cancer immunosurveillance, due to their immunomodulatory potential through a broad range of effector and regulatory functions. Yet, their use as targets or vectors for cancer immunotherapy in cancer yielded inconsistent outcomes, due to potential tumor immune escape mechanisms. Limited information is available regarding the potential dysfunctions of iNKT cells in melanoma patients, and their clinical significance. A better understanding of iNKT cell biology and subversion in these patients would help designing new immunotherapies and improving clinical translations.MethodsHere, we depicted extensive phenotypic, metabolic and functional features of circulating and tumor-infiltrating iNKT cells in melanoma patients, and assessed their clinical relevance.ResultsWe observed that iNKT cells infiltrated melanoma tumors in a gender- and site-dependent manner, and were associated with poor clinical outcome. Invariant NKT cells exhibited a higher basal activation status together with a skewed expression of NK receptors (NKR), NKG2 and immune checkpoints (ICP), as well as a shift toward regulatory iNKT (iNKTreg) cell profile in the melanoma microenvironment. We identified LAG3, CTLA4 and TIM3 as critical negative prognosis factors of clinical evolution. Moreover, tumor-infiltrating iNKT cells displayed a dampened metabolic activity with a decreased glycolysis dependency; such perturbed energetic metabolism impacted patient clinical outcome. Furthermore, iNKT cells revealed distinct metabolic profiles depending on their activation status and ICP profile, underlining critical connections between iNKT cell features and metabolic pattern.DiscussionOverall, our study reveals major phenotypic and metabolic disturbances of circulating and tumor-infiltrating iNKT cells in melanoma, with clinical impacts. By unveiling new key features and skewing details on iNKT cells in melanoma, our study paves the way for innovative combination strategies exploiting metabolic pathways and/or disturbed ICP profiles to overcome immune subversion and better harness the potential of iNKT cells for cancer immunotherapy.